DO CONSUMERS ABANDON SHIP AFTER A CELEBRITY ENDORSEMENT SCANDAL: EVIDENCE FROM AN EMERGING MARKET (Third Sector Social Economic Review, 2019)
Celebrity endorsement is an effective method of advertising due to the great influence they exert over the members of a  society. The success of a brand can be completely intertwined with the success of a celebrity.  The research  investigates the effectiveness of  celebrity endorsements as a method of promotion in the minds of consumers today. Another major goal of this research is to explore whether Turkish consumers are affected by celebrity scandals and will continue similar purchase behaviour subsequent to the publicizing of a scandal. Descriptive research is conducted on a sample of 390 participants to establish the overall attitudes, and purchase behaviour of Turkish consumers.Through the data obtained via face-to-face surveys, it is concluded that the majority of consumers are highly critical about the private lives of celebrities and when a celebrity is involved in a scandal, this ultimately leads to an adverse influence on the decision to purchase a product or service endorsed by that celebrity. The results from this study has confirmed that there is a great risk for companies who use celebrity endorsements in the Turkish market, since consumers care significantly when the reputation of a celebrity is tarnished. Companies need to figure out how to distance themselves from a celebrity and do damage control following the eruption of  a scandal in order to avoid the collapse of their brands.
Keywords: Purchasing decision; young Turkish consumers; celebrity endorsement; celebrity scandal